Impact of interfacial layer and transition region on gate current performance for high-K gate dielectric stack its tradeoff with gate capacitance. - Yang-Yu Fan (IEEE Transactions on electron devices)
Stacked gate dielectrics are modeled with respect to the impact on the leakage current of interfacial layers and transition regions, considering the tradeoff with the gate capacitance. A Franz 2-band dispersion model is used. Low-EOT and low-gate-current regimes are explored theoretically using reasonable estimates guided by experimental data. Transition layer values of each parameter are qualitatively explored for oxynitride, Si3N4/SiO2, and high-K stacks. Higher dielectric constant and more insulating materials are obviously desired for each layer of dielectric; however, the transition region becomes more important as such dielectrics are considered. Higher dielectric constant of interfacial layer is desirable for the low-EOT-low-gate-current requirement.